Crystallization - Mullin, J. W. (John William) (Oxford ; Boston : Butterworth-Heinemann, 2001)
Since the first publication of this definitive work nearly 40 years ago, this fourth edition has been completely rewritten. Crystallization is used at some stage in nearly all process industries as a method of production, purification or recovery of solid materials. Incorporating all the recent developments and applications of crystallization technology, Crystallization gives clear accounts of the underlying principles, a review of the past and current research themes and guidelines for equipment and process design. This new edition introduces and enlarges upon such subjects as: Control and Separation of polymorphs and chiral crystals Micro- and macro-mixing and the use of computer fluid dynamics Seeding and secondary nucleation in batch crystallization processes Incorporation of upstream and downstream requirements into design procedures for crystallization plant Computer-aided molecular design and its use in crystal habit modifier selection Crystallization provides a comprehensive overview of the subject and will prove invaluable to all chemical engineers and industrial chemists in the process industries as well as crystallization workers and students in industry and academia. Crystallization is written with the precision and clarity of style that is John Mullin's hallmark - a special feature being the large number of appendices that provide relevant physical property data. Covers all new developments and trends in crystallization. Comprehensive coverage of subject area.
The crystalline state -- Physical and thermal properties -- Solutions and solubility -- Phase equilibria -- Nucleation -- Crystal growth -- Recrystallization -- Crystallization techniques -- Processes and equipment -- Crystallizer operation and design -- Control and Separation of polymorphs and chiral crystals -- Micro- and macro-mixing and the use of computer fluid dynamics -- Seeding and secondary nucleation in batch crystallization processes -- Incorporation of upstream and downstream requirements into design procedures for crystallization plant -- Computer-aided molecular design and its use in crystal habit modifier selection -- Appendices comprising many tables of useful data including solubility, density, viscosity, diffusivity, activity, conductivity, heats of solution and fusion, common names of crystalline materials -- References.
Includes bibliographical references (p. [536]-575) and indexes.
Keywords: Crystallization; Electronic books